A Stress Management and Smart Management in Prevention and Control of Hypertension - Suwito, Joko; Mu'afiro, Adin; Hidayati, Sri; Waluyo, Kiaonarni Ongko (Frontiers in Community Service and Empowerment, 2025)
Through this community service, it is attempted to make the community accustomed to implementing CERDIK behavior in daily life and can make efforts to control psychological stress to prevent hypertension and control blood pressure fluctuations even though they have routinely taken antihypertensive medication. The purpose of this community service activity is to improve the competence of health cadres who provide daily education and assistance and strive to increase the role of the community independently in controlling stress and getting used to CERDIK behavior to prevent and control hypertension incidents in the community in the Tambakrejo Sutabaya Health Center area, with one Surabaya Hebat Health Cadre. The service method used is to provide training and at the same time assistance to the target Surabaya Hebat Health Cadre, in order to provide education, assistance, training in controlling psychological stress and CERDIK behavior, with an emphasis on routine health checks (checking random blood sugar, blood cholesterol, blood pressure, acute psychological stress conditions), Diligent activities and sports (by encouraging hypertension gymnastics once a week in the hypertension community group), and Managing stress (with the Affirmation-tapping method) and refreshment to maintain the behavior that exists in CERDIK. Activities related to increasing the caregiver's ability to care for the elderly who experience daily problems related to psychological approaches and the like have never been carried out. Supported by the results of research conducted at the Nursing Home for the Elderly, it showed that there was a difference between pre and post-test in the group that received guidance or counseling treatment on the happiness of the elderly with a significant value. The purpose of this training is to empower elderly caregivers at Nursing Home at St. Yosef, Surabaya, and identifying the effectiveness of the guidance model (Guidance) by caregivers. The number of participants is 50 people. The method used is. Discussions, demonstrations, skills training, and evaluation of skills. The result of training for caregivers is an increase in knowledge-based on pre-test and post-test scores. There was an increase in skills seen in four skills, namely communication in the elderly, active movement, passive movement, mobilization, and daily activity training. The implication of this activity is to increase the knowledge and skills of caregivers in providing care for the elderly through effective communication with the elderly in nursing homes as an effort to improve their health of the elderly .